DAMPAK UKURAN DEGREE OF FINANCIAL LEVERAGE, SALES GROWTH, DAN SIZE GROWTH TERHADAP RETURN HARGA SAHAM - Indra Widjaja (Universitas Trisakti, 2011)
The effects of financial reports on stock price is a big issue of research in finance and investment management. A number of studies investigate how financial information becomes impounded in security prices and affects investment decisions. This research examines the relationship between degree of financial leverage, sales growth, size growth and stock return of listed companies in infrastructure, utility and transportation sector in Indonesia Stock Exchange. The research uses combined data, which consists of time series with cross section or known as panel data. Final result indicates that sales growth and size growth influences stock return positively but not significantly. Beside that degree of financial leverage influences stock return negatively and significantly.Keywords : Degree of financial leverage, Sales growth, Size growth and infrastructure, Utility and transportation sector